2019
DOI: 10.1021/acs.jpcb.9b04071
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Glycerol Binding within the Active Site of Coenzyme B12-Dependent Diol Dehydratase

Abstract: Molecular dynamics (MD) simulations have been employed for the first time to gain insight into the geometry of glycerol (GOL) bound within the active site of B 12 -dependent diol dehydratase (B 12 -dDDH). A peculiar feature of the B 12 -dDDH enzyme is that it undergoes suicidal inactivation by the substrate glycerol. To fully understand the inactivation mechanism, it is crucial to identify all possible interactions between GOL and the surrounding amino acid residues in the enzyme−substrate complex. Particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…Therefore, engineering an enzyme that is resistant to inactivation should be an important research direction in applying coenzyme B 12 -dependent GDHts for industrial processes. Structural and computational studies have demonstrated that the conformation of glycerol plays a role in GDHt inactivation (Bachovchin et al, 1977;Bilicì et al, 2019). Mutations were introduced at the active site of coenzyme B 12 -dependent DDHt to favor its interaction with the pro-R conformation, and the variants showed slower inactivation rates than the wild-type enzyme even though their activities decreased (Yamanishi et al, 2012).…”
Section: Perspectives On the Engineering Of Coenzyme B 12 -Dependent mentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, engineering an enzyme that is resistant to inactivation should be an important research direction in applying coenzyme B 12 -dependent GDHts for industrial processes. Structural and computational studies have demonstrated that the conformation of glycerol plays a role in GDHt inactivation (Bachovchin et al, 1977;Bilicì et al, 2019). Mutations were introduced at the active site of coenzyme B 12 -dependent DDHt to favor its interaction with the pro-R conformation, and the variants showed slower inactivation rates than the wild-type enzyme even though their activities decreased (Yamanishi et al, 2012).…”
Section: Perspectives On the Engineering Of Coenzyme B 12 -Dependent mentioning
confidence: 99%
“…In another computational study, Biliæ et al also reported the interaction of the two conformations of glycerol at the active site of Kp DDHt with respect to the orientation of the C3-OH group. The OH group in the pro- S conformation was oriented toward Ser301 of the α-subunit, and that in the pro- R conformation was oriented toward Asp335 ( Figures 7C,D ; Bilicì et al, 2019 ). An attempt was made to introduce mutations into coenzyme B 12 -dependent DDHt to favor its interaction with the pro- R conformation of glycerol ( Yamanishi et al, 2012 ), which will be described later.…”
Section: Molecular Understanding Of the Dehydration Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation led to our subsequent classical MD simulation study which detailed the binding geometries of pro(R)-and pro (S)-GOL and (R)-and (S)-1,2-PDO in B 12 -dDDH with AdoCbl and CNCbl as the cofactors. [26] In all model systems containing the Figure 1. Accepted mechanism of B 12 -dDDH glycerol catalysis (green arrows) and the inactivation mechanism proposed by Doitomi et al [17] (red arrows).…”
Section: Introductionmentioning
confidence: 99%